Effectiveness of Hyaluronic Acid Nasal Drops in Post Functional Endoscopic Sinus Surgery - Dian Yusnita; Anna Mailasari Kusuma Dewi; Riece Hariyati (Fakultas Kedokteran Universitas Brawijaya, 2022)
Functional Endoscopic Sinus Surgery (FESS) is commonly performed on patients with chronic rhinosinusitis (CRS) that has not improved through medical treatment. Hyaluronic acid (HA) has a vital role in wound healing and mucosa repair. This study aimed to determine the effectiveness of nasal drops using HA on clinical symptom scores, quality of life, and endoscopic features in post-FESS patients. This study was conducted with a pre- and post-test randomized control group design in 50 CRS patients undergoing FESS (25 males, 25 females, aged 18 to 55 years) at Dr. Kariadi General Hospital Medical Center Semarang from May to November 2019. The treatment group received additional HA therapy, while the control group only received standard therapy. Subjects were assessed with clinical symptom scores, quality of life, and endoscopic features before and after treatment. The statistical analysis was performed between the control and treatment groups using the Mann-Whitney test. There were significant differences between the control and treatment groups on clinical symptom scores (nasal congestion p = 0.001, runny nose p = 0.027) and endoscopic features (edema p = 0.001, secret p = 0.001, crusts p = 0.001). The therapy in post-FESS patients was using nasal drops, the treatment group was given HA, and the control group was given a placebo. Nasal drops using HA in the treatment group show improvement in clinical symptom scores of nasal congestion and runny nose, as well as the endoscopic appearance of edema, secret, and crusts.